2020
DOI: 10.3390/jcm9092995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statin Use on the Clinical Manifestations, Laboratory Test Results and Outcome of Lyme Neuroborreliosis

Abstract: Statins have anti-inflammatory and potentially antimicrobial activity, but whether they have a beneficial effect on the course of infectious diseases is controversial. In this study, we assessed the impact of pre-existing statin use on the course and outcome of Lyme neuroborreliosis manifested as meningoradiculitis (Bannwarth’s syndrome). One hundred and twenty three consecutive patients with Bannwarth’s syndrome, of whom 18 (14.6%) were being treated with statins, were included in the study. To assess the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…We are not aware of any clinical study of the effect of statin use on the progression and outcome of early LB, manifesting as EM. However, it was recently reported that statin use is not associated with clinical manifestations, laboratory test results, and outcome in patients with Bannwarth’s syndrome [ 13 ], which is consistent with our results. Experimental studies, on the other hand, have shown that simvastatin and lovastatin have an inhibitory effect on borrelial growth in vitro [ 8 ] as well as promote clearance of borreliae in a murine model of LB [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We are not aware of any clinical study of the effect of statin use on the progression and outcome of early LB, manifesting as EM. However, it was recently reported that statin use is not associated with clinical manifestations, laboratory test results, and outcome in patients with Bannwarth’s syndrome [ 13 ], which is consistent with our results. Experimental studies, on the other hand, have shown that simvastatin and lovastatin have an inhibitory effect on borrelial growth in vitro [ 8 ] as well as promote clearance of borreliae in a murine model of LB [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is not known whether the anti-borrelial effects of statins found in in vitro conditions and in animal models are applicable to humans, or if hyperlipidemia is associated with progression of borrelial infection in humans. Statin pretreatment was recently found to not be associated with clinical manifestations, laboratory test results, and outcomes in patients with Bannwarth’s syndrome [ 13 ].…”
Section: Introductionmentioning
confidence: 99%